Analysis Of Hospital Health Care, Health Facilities Level I Of BPJS Patients Satisfaction In Sikumana Public Health Centre Kupang - Oktaviana Manek (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Good health care is a community need and is often a measure of development success. The purpose of this study was to analyze inpatient health care service level I to the satisfaction of BPJS patients in the Sikumana Health Center in Kupang City. The study was conducted at the Sikumana Community Health Center in Kupang City from 15 October to 10 November 2019. The research design used was a qualitative study using a cross sectional approach. The independent variable is health service and the dependent variable is patient satisfaction. The population of all BPJS patients in the Sikumana Kupang health center in the January-August period was 230 respondents. The sampling technique used was Simple Random Sampling with a sample of 146 respondents data analysis techniques using the Logistic regression test. The results of the study of 146 respondents the majority (56.2%) of respondents were very satisfied with the service of nurses, there were 82 research subjects, the majority (58.9%) of respondents were very satisfied with the service of doctors namely there were 86 research subjects and the majority (56, 2%) respondents are very Satisfied with Nurse services, there are 82 research subjects, almost half (45.9%) respondents get good service based on Tangibels, almost half (43.2%) respondents get good service based on reliability, most ( 54.1%) respondents get good service based on Responsiveness, almost half (46.6%) respondents get good service based on Assurance and almost half (44.5%) respondents get good service based on Empathy. Logistic regression data analysis concluded that BPJS patient satisfaction based on health services at the Community Health Center in Sikumana, Kupang, obtained a p value of 0.002 because p value <α (0.05) It is expected that research sites will improve the cleanliness of the ward each morning before the examination and in the afternoon, especially the bathroom of the patient and the staff must be diligent in controlling hygiene